1991
DOI: 10.2337/diab.40.7.825
|View full text |Cite
|
Sign up to set email alerts
|

New Potent α-Glucohydrolase Inhibitor MDL 73945 With Long Duration of Action in Rats

Abstract: Inhibition of intestinal alpha-glucohydrolase activity is one approach for reducing the glycemic response from dietary carbohydrate and may prove useful for the treatment of diabetes mellitus. In this article, we describe the pharmacological properties of a time-dependent intestinal alpha-glucohydrolase inhibitor, MDL 73945. When preincubated 2 h with a rat intestinal mucosa preparation before substrate addition, MDL 73945 was a potent inhibitor of sucrase, maltase, glucoamylase, and isomaltase activities (MDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 0 publications
0
27
1
1
Order By: Relevance
“…No Kj va lues were determined, the figures cited being relative values for the inhibitory effect in comparison to acarbose. These data differ in a few cases from so me results in the literature, which are also not always consistent (LEMBCKE et al 1985;SCOFIELD et al 1986;SAMULITIS et al 1987;YOSHIKUNI et al 1988;ROBINSON et al 1991ROBINSON et al , 1992. This is partly due to the fact that the disaccharidases used are not pure enzymes and originated from the sm all intestines of various mammalian sources (pig, rabbit, rat, mouse).…”
Section: -Deoxynojirimycincontrasting
confidence: 56%
See 2 more Smart Citations
“…No Kj va lues were determined, the figures cited being relative values for the inhibitory effect in comparison to acarbose. These data differ in a few cases from so me results in the literature, which are also not always consistent (LEMBCKE et al 1985;SCOFIELD et al 1986;SAMULITIS et al 1987;YOSHIKUNI et al 1988;ROBINSON et al 1991ROBINSON et al , 1992. This is partly due to the fact that the disaccharidases used are not pure enzymes and originated from the sm all intestines of various mammalian sources (pig, rabbit, rat, mouse).…”
Section: -Deoxynojirimycincontrasting
confidence: 56%
“…Pharmacokinetic parameters, especially absorption from the gastrointestinal tract, enterohepatic circulation, rate of enzyme synthesis, etc., all play a (ROBINSON et al 1991). In contrast the 1-deoxynojirimycin derivative 93 (emiglitate) is still active if it is administered 17 h before the sucrose loading, possibly because it is recycled to the intestinal enzymes via the enterohepatic circulation.…”
Section: -Deoxynojirimycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful results were first obtained with miglitol and emiglitate. The ED 50 was evaluated respectively as 0.24 and 0.16 mg/kg body weight [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Of the two popular glucosidases, α-glucosidase (EC 3.2.1.20) has drawn a special interest of the pharmaceutical research community because it was shown in earlier studies that the inhibition of its catalytic activity resulted in the retardation of glucose absorption and the decrease in postprandial blood glucose level. [3][4][5] Therefore, effective α-glucosidase inhibitors may serve as chemotherapeutic agents for clinic use in the treatment of diabetes and obesity. Due to the catalytic role in digesting carbohydrate substrates, α-glucosidase has also been well appreciated as a therapeutic target for the other carbohydrate mediated diseases including cancer, 6 viral infections, 7,8 and hepatitis.…”
Section: Introductionmentioning
confidence: 99%